Influence of production batch related parameters on static and fatigue resistance of LPBF produced AlSi7Mg0.6. (December 2022) - Cacace, Stefania; Gökhan Demir, Ali; Sala, Giuseppe; Mattia Grande, Antonio
Highlights: Static and fatigue performances of AlSi7Mg0.6 from additive manufacturing were investigated by a large testing campaign. Fatigue tests confirmed the influence of part orientation and position on stress-relieved and sandblasted AlSi7Mg0.6 specimens. Fractography analysis showed characteristic defects for samples with different building orientation. Abstract: In laser powder bed fusion (LPBF), the influence material properties are often determined as a function of the inclination with respect to the build direction. In industrial production with variable component shapes and dimensions, the part orientation will often be a matter of the available space in the build volume. Additionally, build-to-build variability is an important factor that may impact the mechanical properties that are often not quantified. Such sources of variability are of great importance for highly demanding sectors such as aviation and aerospace, where lightweight Al-alloys are often used with the geometrical freedom given by the LPBF process. Hence, this work systematically investigates the influence of production batch-related parameters together with part inclination in the LPBF of AlSi7Mg0.6 alloy. Three builds were executed to quantify the impact of the batch, part position, and inclination on the static and fatigue resistance of the alloy in a completely randomized experimental design using an industrial LPBF machine. The results were analysed by the appropriate statistical methods both for discrete and functional data. The results showed that while the part orientation only influenced the static properties, the part position significantly affected the fatigue life demonstrated by the different low cycle fatigue life coefficients.